Suplementasi Zinc dalam Penyembuhan Gejala Pneumonia pada Anak - Deshiana Az-Zahra Putri Wildani; Mirasari Putri; Riri Risanti (Bandung Conference Series: Medical Science, 2022)
Abstract. The high death cases of children aged under five years in the world caused by pneumonia. Children are vulnerable to infection due to developing immunity and low nutritional intake. Micronutrients such as zinc play a role in the development of the immune system against infectious diseases. Scoping review, as the study used aims to determine the provision of zinc supplementation as adjuvant therapy in healing symptoms of pneumonia in children. Scoping review, as the study used aims to determine the provision of zinc supplementation as adjuvant therapy in healing symptoms of pneumonia in children. The articles were searched through the database, then screened, followed by a critical assessment. Seven of the 83,594 articles between the years 2010-2021 were analyzed. The results of the analysis showed three articles proved that zinc administration could fight pneumonia by increasing the body's defense system and limiting the excessive inflammatory response so as to accelerate the healing duration of pneumonia symptoms in children, while other articles did not show the effect of zinc on pneumonia symptoms. The conclusion is that only three of the seven articles show the benefits of zinc supplementation by accelerating the duration of healing of pneumonia symptoms in children. Abstrak. Tingginya kasus kematian anak usia di bawah lima tahun di dunia disebabkan oleh pneumonia. Anak rentan terhadap infeksi akibat imunitas masih berkembang serta asupan nutrisi rendah. Mikronutrien seperti zinc berperan dalam perkembangan sistem imun untuk melawan penyakit infeksi. Scoping review, sebagai studi yang digunakan bertujuan mengetahui pemberian suplementasi zinc sebagai terapi adjuvant dalam penyembuhan gejala pneumonia pada anak. Dilakukan pencarian artikel melalui database, lalu diskrining, selanjutnya dilakukan penilaian kritis. Didapatkan tujuh dari 83.594 artikel antara tahun 2010-2021 yang akan dianalisis. Hasil analisis menunjukan tiga artikel memperlihatkan pemberian zinc dapat melawan pneumonia dengan meningkatkan sistem pertahanan tubuh dan membatasi respon inflamasi berlebih sehingga dapat mempercepat durasi penyembuhan gejala pneumonia anak, sementara artikel lain tidak memperlihatkan efek zinc terhadap gejala pneumonia. Simpulan yang didapat adalah hanya tiga dari tujuh artikel yang menunjukkan manfaat pemberian suplementasi zinc dengan mempercepat durasi penyembuhan gejala pneumonia anak.